Re-Visiting the Role of Education on Poverty Through the Channel of Financial Inclusion: Evidence From Lower-Income and Lower-Middle-Income Countries - Shi, Zheng; Qamruzzaman, Md. (Frontiers in Environmental Science, 2022)
For attaining sustainable economic development in the lower and lower-middle-income nations, the role of poverty reduction has been critically addressed along with the economic determents that manage poverty level which has accelerated the economic progress by ensuring the higher performance of other macrovariables including FDI inflows, financial development, trade openness, and human capital accumulation. The purpose of this study was to evaluate the role of education and financial inclusion in poverty reduction in lower and lower-middle-income countries for the period 1995–2018, with a panel of 68 nations. The study applied several econometrical tools, including a cross-sectional dependency test (CDS), panel unit root test, panel cointegration test, generalized methods of moment (GMM), and system-GMM. The CDS results confirmed the sharing of typical dynamics in research units. The test of stationarity detected variables was integrated after the first difference. A panel cointegration test documented the long-run association between education, financial inclusion, and poverty. The study documented that government investment in education positively assists poverty reduction, implying a negative association between them. Furthermore, the inclusion of the population into the formal financial system expedited the poverty reduction process that has access to formal financial benefits allowing earning opportunities and higher purchasing power, eventually supporting an increased standard of living. Directional causality tests revealed feedback hypothesis holds in explaining the nexus between education, financial inclusion, and poverty, i.e., [ED←→Poverty; FI←→Poverty]. For policy reform and restructuring, it is essential to pay considerable attention to development in education and access to the formal financial system because progress in education and finance has positive spillover effects on the aggregated economy.